The Narkotising Impulse Threshold Values of Certain Fresh Water Fishes - NAMBOODIRI, K. SREEDHARAN; VERGHESE, M. D. (Fishery Technology, 2025)
The effect of impulse current on the fish at a particular impulse rate and voltage depends on the size and kind of the fish. It is directly proportional to the temperature and inversely proportional to the conductivity of the medium.